The Relationship between Socioeconomic and Nutritional Status with the Incidence of Pulmonary Tuberculosis at the Nangkaan Public Health Center Bondowoso - Damon Wicaksi; Yuni Priyo Wahyudi; Shelly Dwi Kurniawati Atmadja (Universitas Bondowoso, 2022)
Introduction:Tuberculosis lungs are still a major public health problem in Indonesia. The incidence of pulmonary tuberculosis continues to increase as well as the incidence of pulmonary tuberculosis at the Nangkaan Bondowoso Health Center every year there is always an increase. The purpose of this study was to analyze the relationship between socioeconomic status and nutritional status with the incidence of pulmonary tuberculosis. Method: Research design is cross sectional. Data collection was taken from medical records of patients with pulmonary tuberculosis at the Nangkaan Health Center which was held from October to November 2021 with a population of 56 people. The sample used is total sampling. Data collection techniques with questionnaires and observations, then the data were analyzed by ANOVA test. Result: Based on the data obtained, most of the respondents socioeconomic levels are low socio-economic as many as 51 people (91%), while most of the respondents' nutritional status is poor nutrition status as many as 44 people (78%), and the incidence of pulmonary tuberculosis is mostly with positive BTA as many as 49 people (87%). From the results of the ANOVA test, it was found that there was a significant relationship between socioeconomic status and nutritional status with the incidence of pulmonary tuberculosis at the Nangkaan Bondowoso Public Health Center with p-values ​​of 0.16 and 0.00 (p-value <0.05). Conclusion: Low socioeconomic status will affect the low nutritional status of patients with pulmonary tuberculosis and can worsen the body's immunity which has an impact on increasing the risk of transmission of pulmonary tuberculosis.